Educational Programming to Prevent Violence in Schools in the United States: An Analysis of School Health Profiles - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
This repeated, cross-sectional study examined trends in the availability of school-based programming to prevent violence in middle and high schools across the United States from 2008 to 2020. Overall, violence prevention programming increased in respondent schools throughout the study period. However, important gaps remain, with lingering state-level disparities.
Keywords: Human factors and ergonomics; Injury prevention; Occupational safety and health; Poison control; Respondent; Suicide prevention; adolescent health; dept.hms; health education; school violence prevention; teacher training; youth violence prevention

Reply - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott; Benes, Sarah (The Journal of Pediatrics, 2025)
Keywords: dept.hms

Trends in school mental health and substance use education - Gao, Chloe; Szlosek, Donald; Zhong, Anthony; Hadland, Scott E.; Benes, Sarah S. (JAMA, 2025)
The percentage of US youths experiencing mental health and substance use problems has risen rapidly in recent years. Schools are important settings for prevention, but whether preventive programming meets student needs is unknown. This study examined trends in school programming related to mental health and substance use and teacher professional development across US middle and high schools from 2008-2020.
Keywords: dept.hms; peer-reviewed